The Peel Watershed Case: Implications for Aboriginal Consultation and Land Use Planning in Alberta - Jaremko, Sara L. (Canadian Institute of Resources Law, 2017)
Occasional Paper #56 funded by Alberta Law Foundation, updated December 1, 2017 to include SCC decision. As in Alberta, the Government of the Yukon has been working on comprehensive land-use planning legislation. The Yukon Court of Appeal decision considered the Peel Watershed Regional Plan that covers a large underpopulated and largely undeveloped area of the Yukon, with the potential for oil and gas and hard rock mineral development, in the context of the duty of the Crown to consult with First Nations communities in the land use planning process. This publication reviews the Peel Watershed decision and its implications for land use planning and consultation with the First Nations in Alberta. The paper addresses issues that include the status of land use planning consultation as a treaty right, procedural vs. substantive breaches of the duty to consult, and the potential for unilateral Crown decision-making in both contexts. The broader “spirit” of government obligation, the “honour of the Crown,” is considered in light of the recent SCC court decision.